Tracing the path between coaching and performance a study of coaching in an inbound call center program - Sy Su, Chadwick Co 1981- (2009.)
"The study's mileu was set in an inbound call center program. A survey was administered to 61 agents to measure the variables of coaching frequency, coaching duration, Coaching content, Coach Competency Perception, Coaching Resources, Coaching Recipient's Efficacy and Coach-Coachee Relationship. These variables, along with Agent Rank, Agent Tenure, Coach Rank and Coach Tenure, were analyzed for their effect on the agents' performance. The survey was substantiated by the findings from interviews with 15 key agent-informants. It was found both quantitatively (through regression analyses) and qualitatively (through key informant interviews) that Coaching Recipient's Efficacy had the biggest effect on the agent's performance, followed by Coaching Content and Coaching Resources. The other variable were of little or no effect. It was also found that even as the coaches in the study's milieu used a rather limited set of tools when coaching their agents, the agents did recognize the coaches' expertise and advantage in terms of experience. It is concluded that while coaching does have an effect on performance, any claim that it alone is the explanation for performance is tenuous at best."
Thesis (M.A. Communication Research)--University of the Philippines, Dililman.
Vita.
Keywords: Employees -- Coaching of; Employees -- Training of; Performance; Call centers -- Personnel management -- Philippines; Customer services -- Management -- Philippines